Quests for impossible wholeness: time, memory, and in-betweenness im Marcel Proust's A la Recherche du Temps Perdu and Ahmet Hamdi Tanpınar's Huzur - Özbek, Esen Egemen. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
This thesis scrutinizes Marcel Proust and Ahmet Hamdi Tanpınar's conceptions of time with a particular interest in the experience of modernity. The primary sources studied in this thesis are Proust's A la recherche du temps perdu (In Search of Lost Time) and Tanpınar's Huzur (Peace of Mind). Moreover, in order to shed more light on Tanpınar's thought his articles are also investigated. The study incorporates literary and historical analyses to contextualize both authors' works. The main problem of the study is to investigate the impact of the experience of modernity on temporality. For this end, this thesis, first of all, accounts the historical transformation of the perception of time. It is possible to maintain that the experience of modernity was constructed upon a specific time perception and that this experience brought with fragmentation, transitoriness, and loss of stable ground. Proust and Tanpınar's works are tried to be situated in this context. The thesis argues that within this modern temporality dominated by transitoriness and elusiveness Proust and Tanpınar try to find a stable anchoring point that would resist the cruel order of time. The way of finding this stable point and wholeness is constructing links between the past and the present that would constitute the temporal continuity that they are in search of. However, both novels demonstrate that the quest for wholeness is an impossible one because wholeness is once broken and there is merely the memory of it. They are reconstruction of that wholeness in the aesthetic field.
Keywords: Time in literature.; Memory in literature.